Physical Education in primary schools through traditional folk Games in outdoor contexts - Cataldi, Stefania; Poli, Luca; Bonavolontà, Valerio; Fischetti, Francesco (Formazione & insegnamento, 2023)
The purpose of the paper is to highlight the need to change teaching strategies in physical education in elementary school. Sedentary lifestyles, abetted by technology such as the recent COVID19 Pandemic, call for a reevaluation of classical teaching methodologies to promote, from an early age, education toward active lifestyles. After an examination of what folk tradition games (GTD) represent, the analysis reevaluates their use , in the elementary school setting both to foster socialization and preserve folk values and as a practice of physical activity outside the school setting. For this reason, the discussion focuses on innovative teaching strategies such as outdoor education (OE) and the psycho-physical benefits they bring, along with the practice of GTDs, as real educational experiences in authentic situations. The use of GTDs in OE can be an ecological strategy to promote motor activity as an active lifestyle in a sensitive age such as childhood.